Creative trade's effect on a few macroeconomic factors in China - Khudhair Abbas Hussein Al Waeli; Salam Kazem Shani; Sultan Jasem Sultan; Ali Omran Hussein (Heritage and Sustainable Development)
Creative trade has witnessed significant development in the last years of the twentieth century, occupying a large portion of the global trade balance due to the significant development in innovation and the advancement of talent and knowledge. Its share has reached 3% of global GDP, with creative sectors growing significantly in some countries. Creative trade has also achieved significant growth, leading to increased EG rates in these countries. Using ARDL model, the study attempts to examine how China's creative commerce has developed and how it affects investment and EG. This model utilizes data on creative exports and imports, GDP, and investment for the Chinese economy. Of the several findings of the study, the most significant is that China's creative trade balance has been in surplus over the analysis period. It also demonstrates the long-term equilibrium between private investment and growth, as well as between imports and innovative exports. Additionally, in the long run, exports and revenues have a positive impact on China's economy.